Determinants Of Community Health Center Utilization In The Working Area Of The Meukek Community Health Center, South Aceh Regency - Cut Rahmi; Rasima Rasima; Asmanidar Asmanidar (International Journal of Multidisciplinary Sciences and Arts, 2025)
The importance of utilizing Community Health Centers (Puskesmas) in a region to the community is to help the community recognize their health problems as early as possible, as well as find and determine their management efforts, in addition to providing convenience and the ability to access quality health care facilities fairly and equitably. With the hope that the community is able to independently overcome their health problems, the community lives in an environment with healthy behavior, and encourages the community to participate in efforts to improve their health status as high as possible. The community's utilization of health services such as Puskesmas is influenced by several factors, including: the socioeconomic level of the family, the quality of health services at the Puskesmas, distance to the service center, a pleasant attitude, and, in accordance with community demands, the organization and management of the Puskesmas, and the range of rates. Utilization of Puskesmas is also influenced by internal factors such as age, education, knowledge, and attitudes, as well as external factors such as family support and socioeconomic status. This study aims to identify factors related to the utilization of Puskesmas by the community in the working area of ??the Puskesmas, Meukek District, South Aceh Regency. The design in this study uses a descriptive correlational design with a Cross-sectional study approach. The study population was all patients (community) who sought treatment at the Meukek District Community Health Center, South Aceh Regency, with a sample of 96 people, using a purposive sampling technique. The instrument used in this study was a questionnaire containing the respondent's identity and research variables consisting of the accessibility of the Community Health Center, knowledge, family support, and quality of service. Data collection techniques were carried out using questionnaires and interviews with respondents. Data analysis through univariate analysis using the frequency distribution formula and bivariate analysis using the Chi-Square statistical test with a degree of significance (?) = 5% to identify factors related to the use of the Community Health Center by the community in the working area of ??the Community Health Center, South Aceh Regency.